The Effects of Exercise Regimens on Irisin Levels in Obese Rats Model: Comparing High-Intensity Intermittent with Continuous Moderate-Intensity Training. (27th December 2018) - Tine Kartinah, Neng; Rosalyn Sianipar, Imelda; Nafi'ah,; Rabia,
Abstract : Background. Recently, high-intensity intermittent training (HIIT) appears to have the same beneficial effects or even superior to those of continuous moderate-intensity training (CMIT) on body fat mass reduction. Exercise may induce myokine secretion such as irisin, which plays a role as a mediator of beiging process, and thus might contribute as treatment of obesity. However, the effects of those exercise formulas on irisin level changes as beiging agent are not known. In addition, metabolic states may affect the irisin responses to those exercise formulas. Therefore, this study was aimed to determine the different effects of exercises using HIIT and CMIT on circulating and tissue irisin levels in normal and abnormal metabolic conditions (obese). Methods. Sixteen male Sprague-Dawley rats (8 weeks of age) were randomized to 4 groups according to training regimens (HIIT and CMIT) and metabolic conditions (normal and abnormal/obese). The groups are (1) HIIT on normal metabolic (n=4), (2) CMIT on normal metabolic (n=4), (3) HIIT on abnormal metabolic (n=4), and (4) CMIT on abnormal metabolic (n=4). Abnormal metabolic condition was induced with high fat diet (19% fat) for 8 weeks in obese rats. Irisin levels in serum, skeletal muscle, and white adipose tissue were evaluated by ELISA. Results. Serum irisin levels were shown significantly higher in normal metabolic compared to abnormal metabolic condition (P<0.001). The effect of interaction between metabolic condition and exercise formula was found (P<0.01) on adipose irisin levels. The effect of HIIT was shown significantly more effective on adipose irisin levels, compared with CMIT in abnormal metabolic conditions. However, no significant differences of skeletal muscle irisin levels were found in both normal and abnormal metabolic subjects (P>0.05). Regarding exercise formula, no different effects were found between HIIT and CMIT on skeletal muscle irisin levels in both metabolic conditions (P>0.05). The similar findings were observed in serum irisin levels (P>0.05). Conclusions. The exercise effects in abnormal metabolic condition might be more adaptable in maintaining the irisin levels in skeletal muscle and induce the irisin uptake from circulation into adipose tissue. In addition, HIIT might be more involved to induce irisin uptake into adipose tissue; thus it might have the significant role in beiging process. However, further research about how the HIIT formula affects the regulation mechanisms of irisin uptake into adipose tissue is still warranted.